2017
DOI: 10.4314/ahs.v17i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing inhibitory activity of sub-inhibitory concentrations of β-lactams

Abstract: Introduction: The virulence factors of Pseudomonas aeruginosa are under the control of quorum sensing (QS) signals. Hence, interference with QS prevents its pathogenesis. Objective: The aim of the present research is to assess the influence of some β-lactam antibiotics on cell communication and the release of different virulence factors. Methods: The minimal inhibitory concentrations of ceftazidime, cefepime and imipenem were evaluated by microbroth dilution method. The effect of sub-inhibitory concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Unexpectedly, none of our treatments showed significant reductions in the production of AHLs in both strains, even though virulence factors controlled by QS seemed to have been reduced. Similar studies report a reduction in QS signal levels in P. aeruginosa by subinhibitory concentrations of antibiotics or adjuvants [72][73][74][75]. El-Shaer et al, for example, reported a reduction in QS signals with PABN alone in P. aeruginosa strains isolated from urinary tract and wound infections [43].…”
Section: Discussionmentioning
confidence: 78%
“…Unexpectedly, none of our treatments showed significant reductions in the production of AHLs in both strains, even though virulence factors controlled by QS seemed to have been reduced. Similar studies report a reduction in QS signal levels in P. aeruginosa by subinhibitory concentrations of antibiotics or adjuvants [72][73][74][75]. El-Shaer et al, for example, reported a reduction in QS signals with PABN alone in P. aeruginosa strains isolated from urinary tract and wound infections [43].…”
Section: Discussionmentioning
confidence: 78%
“…The untreated strains were also grown under the same conditions. Assay of different virulence factors was performed in the presence and absence of the tested compounds ( El-Mowafy et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…QSI activity of azithromycin ( Tateda et al., 2001 ), doxycycline ( Husain and Ahmad, 2013 ), and ciprofloxacin ( Skindersoe et al., 2008 ) have been detected ( Nalca et al., 2006 ). Moreover, β-lactams, ceftazidime, cefepime and imipenem have demonstrate QSI activity at sub-inhibitory concentrations ( Skindersoe et al., 2008 ; El-Mowafy et al., 2017 ; Aleanizy et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pyocyanin secretion, the expression of genes lasB, rhlA, lasI, lasR, rhlI, and rhlR genes and production of biofilm [160] Manilkara zapota Pyocyanin, protease and elastase secretion and production of biofilm [151] Diarylheptanoids from the barks of Alnus viridis and Alnus glutinosa Pyocyanin secretion, twitching motility and production of biofilm [161] Gingerol Exoprotease, rhamnolipid and pyocyanin secretion and biofilm formation [162] Diterpene phytol Pyocyanin secretion, twitching motility and production of biofilm [163] Dovepress antibiotics can reduce the pathogenic factors' expression of P. aeruginosa such as the diminished of exotoxin A secretion, pyocyanin, protease, DNase, and phospholipase C, as well as significantly removing the QS activity of P. aeruginosa. 125 In addition, SICs of tobramycin could block the expressions of rhlI and rhlR genes by decreasing C4-HSL generation. Previous studies have also confirmed the impact of tobramycin, as a signaling molecule, on virulence genes expression in the transcriptional step.…”
Section: Cordiagilletiimentioning
confidence: 99%
“… 124 The SICs of macrolides and β-lactam antibiotics can reduce the pathogenic factors’ expression of P. aeruginosa such as the diminished of exotoxin A secretion, pyocyanin, protease, DNase, and phospholipase C, as well as significantly removing the QS activity of P. aeruginosa . 125 In addition, SICs of tobramycin could block the expressions of rhlI and rhlR genes by decreasing C4-HSL generation. Previous studies have also confirmed the impact of tobramycin, as a signaling molecule, on virulence genes expression in the transcriptional step.…”
Section: Antibiotics As Qsimentioning
confidence: 99%